Monoparesis Post Bronchial Artery Embolization: Clinicoradiological Discordance in Anterior Spinal Artery Infarct—Case Report and Review of Literature - Gupta, Saurabh; Prakash, Siddharth; Mittal, Ashima; Garg, Cherry; Singh, Suryaveer (Journal of Clinical Interventional Radiology ISVIR, 2019)
Bronchial artery embolization (BAE) is an established minimally invasive treatment for massive or recurrent haemoptysis. Anterior spinal artery (ASA) infarct is an uncommon but serious complication of the procedure. The interventional radiologist doing these procedures must be well versed with the bronchial artery anatomy, its variations, and its relation with ASA to avoid this dreaded complication. The authors report a case in which the patient developed monoparesis and mild transient autonomic dysfunction post BAE but magnetic resonance imaging of spine showed diffuse symmetric cord involvement in ASA territory from D1–D4 level.
Keywords: bronchial artery embolization; anterior spinal artery infarct; monoparesis